FALHAS DE EXECUÇÃO DE SERVIÇOS NO PROCESSO CONSTRUTIVO DE EDIFICAÇÕES HABITACIONAIS - Lazzarini, Simone; Hippert, Maria Aparecida Steinherz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Regarding the quality of the final product, and the expectations of customers, civil construction is below what is expected of an industry of its size and importance. Due to the low quality of labor and the low level of manufacturing control, the number of defects is still quite significant in Brazilian constructions. While construction materials in the country have already incorporated the techniques of quality control in their manufacture, the same is not observed in the construction services. This work aims to collect data on errors in the execution of building works, in order to quantify them in an indicator of nonconformities that serves as a benchmark for the company analyzed. It is also hoped to contribute to industry statistics. The methodology used is the collection of non-conformities of execution, detected during the service inspections, and recorded in appropriate forms. The structural masonry service was studied in greater depth in one of the projects, with the nonconformities detailed for each inspection requirement. The results obtained generated a Nonconformity Indicator, expressed in percentage, which indicates the degree of conformity to the requirements expected in each service. Results of this Indicator varied from 0,2% up to 10,1%, depending on the service analyzed.